Respuesta :

qabtt

Remember that slope-intercept form is the form:

[tex]y = mx + b[/tex]


Let's use some operations to try to get our current equation to that form:

[tex]- \dfrac{4}{3} (x + 1) = y - 2[/tex]

  • Set up

[tex]- \dfrac{4}{3} x - \dfrac{4}{3} = y - 2[/tex]

  • Distribute the [tex]- \dfrac{4}{3}[/tex] onto [tex](x + 1)[/tex] using the Distributive Property

[tex]y = - \dfrac{4}{3}x + \dfrac{2}{3}[/tex]

  • Add 2 to both sides of the equation

Our answer is [tex]\boxed{y = - \dfrac{4}{3}x + \dfrac{2}{3}}[/tex].

ACCESS MORE